ANALYSIS OF AN ACTIVE REACTION FOR ANTIGEN ATTACHMENT TO SOLID PHASE CARRIER IN IMMUNOENZYME ANALYSIS. (World Bulletin of Public Health, 2023)
The purpose of the study. The purpose of the experiment is to evaluate the effect of environmental pH on the degree of attachment of antigens of microorganisms to 96-well polystyrene tablets. It was found that for the selection of a solid phase carrier and attachment of an antigen to it, it is necessary to take into account the pH of the environment, which directly affects the level of antigen adsorption